In vitro Assessment of the Safety and Potential Probiotic Characteristics of Three Bacillus Strains Isolated From the Intestine of Hybrid Grouper (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂) - Amoah, Kwaku; Dong, Xiao-hui; Tan, Bei-ping; Zhang, Shuang; Kuebutornye, Felix K. A.; Chi, Shu-yan; Yang, Qi-hui; Liu, Hong-yu; Zhang, Hai-tao; Yang, Yuan-zhi (Frontiers in Veterinary Science, 2021)
Probiotics serving as an alternative to the criticized antibiotics mainly focus on improving animal’s growth and health. After realizing the dangers posed by diseases that have led to lots of economic losses, aquaculture scientists have sought to the usage of probiotics. However, most probiotics are ineffective in eliciting aquatic animals' preferred effects since they are from non-fish sources. Again, there are even a few marine aquatic probiotics. Given this, a study was conducted to investigate the probiotic potential of the bacterial species isolated from the digestive tract of hybrid grouper (Epinephelus fuscoguttatus♀×E. lanceolatus♂). Based on the morphological, biochemical, 16S rRNA sequencing analysis and evolutionary relationships, the isolated species were identified as Bacillus tequilensis GPSAK2 (MW548630), Bacillus velezensis GPSAK4 (MW548635), and Bacillus subtilis GPSAK9 (MW548634), which were designated as GPSAK2, GPSAK4 and GPSAK9 strains, respectively. Their probiotic potentials including their ability to tolerate high bile salt concentration, low pH, high temperatures, adhesion-ability (auto-aggregation and cell-surface hydrophobicity), antimicrobial activity and biosafety test, compatibility test, haemolytic activity, and antibiotics susceptibility test were evaluated. While GPSAK2 and GPSAK9 strains were γ-haemolytic, that of GPSAK4 was α-haemolytic. All the isolates were resistant to low pH (1) and higher bile salt concentration (0.5%), showed higher viability ability after higher temperature exposure (80°C, 90°C, and 100°C), as well as higher cell-surface percentage hydrophobicity and auto-aggregation. All isolates exhibited positive-compatibility with each other signifying their ability to be used as multispecies. The three strains were susceptible to ampicillin (except GPSAK9, which was resistant), penicillin, kanamycin, ceftriaxone, chloramphenicol, erythromycin, clindamycin, furazolidone (except GPSAK2 and GPSAK9, which was moderately susceptible and resistant, respectively), polymyxin B, vancomycin (except GPSAK9, which was resistant), sulfamethoxazole (except GPSAK9 which was moderately susceptible), amikacin, minocycline, ofloxacin, norfloxacin, doxycycline, neomycin, gentamicin, tetracycline, carbenicillin, midecamycin (except GPSAK9, which was moderately susceptible), ciprofloxacin, piperacillin, and cefoperazone. All isolates demonstrated good antimicrobial activity against four pathogens, viz. Streptococcus agalactiae, Streptococcus iniae, Vibrio harveyi, and Vibrio alginolyticus. The results collectively suggest that Bacillus strains GPSAK2, GPSAK4, and GPSAK9 could serve as potential probiotics candidates that can be used to improve the growth and health status of aquatic animals, especially grouper.